2016
DOI: 10.1007/s10433-016-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of abridged mini-mental state examination scales using population-based data from Sweden and USA

Abstract: The objective of this study is to validate two abridged versions of the mini-mental state examination (MMSE): one intended for use in face-to-face interviews, and the other developed for telephonic interviews, using data from Sweden and the US to validate the abridged scales against dementia diagnoses as well as to compare their performance to that of the full MMSE scale. The abridged versions were based on eight domains from the original MMSE scale. The domains included in the MMSE-SF were registration, orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This is not surprising, given that our study measured cognitive functioning in an age range during which individuals still tend to score highly on the MMSE test, whereas a rapid decline in cognitive functioning has been shown to start after age 84 (Santoni et al, 2015). Moreover, the low variation in cognitive functioning may have been exacerbated by our use of an abridged version of the MMSE instrument (Ericsson et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…This is not surprising, given that our study measured cognitive functioning in an age range during which individuals still tend to score highly on the MMSE test, whereas a rapid decline in cognitive functioning has been shown to start after age 84 (Santoni et al, 2015). Moreover, the low variation in cognitive functioning may have been exacerbated by our use of an abridged version of the MMSE instrument (Ericsson et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…The MMSE is a global cognitive screening test in which orientation, memory, naming ability, ability to follow instructions, attention and copying of pentagons is tested [ 24 ]. It is widely used internationally and has been validated in Swedish populations [ 25 ]. The AQT test [ 26 ], a reliable screening test to detect early dementia [ 27 ], is a test of processing speed, attention and executive function.…”
Section: Methodsmentioning
confidence: 99%
“…This was especially noted in the questions related to orientation, registration, visual naming, and free/cued recall. Notably, these are also the cognitive domains which are some of the more sensitive items in the long-established screening tools ( Coleman et al, 2017 ; Ericsson et al, 2017 ; Horton et al, 2015 ). Beyond the conflicts between Indigenous and Western culture and values, the research findings revealed that issues of cultural safety and systemic racism persist and continue to impact the care of older Anishinaabe adults.…”
Section: Discussionmentioning
confidence: 99%